Unexpected {011¯1} pyramidal stacking faults in Zr(Fe, Cr)2 secondary phase particle induced by the C15→C14 Laves phase transformation in Zircaloy-4. (1st April 2023) - Guo, Wenbin; Li, Geping; Ren, Jie; Ali, Muhammad; Hu, Jianan; Wang, Qichen; Yuan, Fusen; Zhang, Yingdong; Han, Fuzhou
Abstract: The formation mechanism of ( 01 1 ¯ 1 )C14 pyramidal stacking faults (SFs) with a 8.6° deflection to the SFs on ( 11 1 ¯ )C15 planes of Zr(Fe, Cr)2 secondary phase particle (SPP) in Zircaloy-4 under cyclic deformation were investigated by using transmission electron microscopy. Results showed that local C14 domain structures can be induced into the C15 SPP when the SFs formed on ( 11 1 ¯ )C15 close-packed planes by the emission of 1 6 [ 112 ] C15 Shockley partial dislocations under cyclic stress effects. Moreover, when the shear stresses along [ 11 2 ¯ ] C15 direction were large enough to initiate the 1 6 [ 11 2 ¯ ] C15 partials on every other (111)C15 planes, the C15→C14 Laves phase transformation would be accomplished, resulting in a significant reconstruction of atomic configurations of the SFs on original ( 11 1 ¯ )C15 planes. Thus, the formation of ( 01 1 ¯ 1 )C14 pyramidal SFs during C15→C14 phase transformation in SPP were presented. Graphical abstract: Image, graphical abstract